One Instructor's Experience with Standard Five... - Irina I. Holden (Issues in Science and Technology Librarianship, 2008)
A personal narrative is presented which explores the author's experience of designing her information literacy courses pursuant to the Information Literacy Standards for Science and Engineering/Technology.